The association of serum Klotho concentrations with hyperlipidemia prevalence and lipid levels among US adults: a cross-sectional study - Shunli Jiang; Yongxin Wang; Zengliang Wang; Lu Zhang; Feng Jin; Bo Li (BMC, 2023)
Abstract Background Klotho has anti-oxidative and anti-inflammatory properties. However, little is known about whether high Klotho concentrations were associated with reduced hyperlipidemia risk and improved plasma lipid levels. Methods Participants with complete data on serum Klotho and plasma lipid concentrations from the 2007-2016 National Health and Nutrition Examination Survey were included. Weighted regression models were fitted to explore the association of Klotho concentrations with hyperlipidemia risk and plasma lipid levels while restricted cubic spline models were applied to explore the dose-response relationship. Additionally, we assessed the mediating effects of C-reaction protein (CRP) on the foregoing association. Results Individuals in the fourth and fifth quintile of serum Klotho had an adjusted odds ratio (OR) of 0.77 (95%CI: 0.65, 0.93) and 0.67 (95%CI: 0.65, 0.93) for hyperlipidemia. Doubling of serum Klotho concentrations was associated with decreased hyperlipidemia risk (OR = 0.81; 95%CI: 0.68, 0.95) and triglyceride levels (13.25 mg/dL; 95%CI: 4.02, 22.47), with a monotonic dose-response relationship. Individuals in the fourth and fifth quintile of serum Klotho had a 0.07 (95%CI: 0.002, 0.13), 0.08 (95%CI: 0.02, 0.15) and 0.05 (95%CI: -0.03, 0.12) mg/dL decreased CRP levels, with a marginally significant trend (P trend = 0.05). Conclusions Higher Klotho concentrations were associated with reduced hyperlipidemia risk and triglyceride levels. Klotho supplementation maybe a promising method to intervene and prevent hyperlipidemia, but the underlying mechanism should be further explored.